2007
DOI: 10.1186/1752-0509-1-50
|View full text |Cite
|
Sign up to set email alerts
|

Noise-induced switches in network systems of the genetic toggle switch

Abstract: Background: Bistability, the capacity to achieve two distinct stable steady states in response to a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 52 publications
1
78
0
Order By: Relevance
“…The origin of stochasticity can be attributed to internal and external noises. It is well known that noise can have great impacts on biological systems' dynamical properties (Lipshtat et al 2006;Hasty et al 2000;Vilar et al 2002;Rao et al 2002;Wang et al 2007;Li and Li 2008), for example, noise can induce sustained stochastic oscillation even though the corresponding deterministic system only yields steady state . In this paper, we have also studied the effect of extrinsic noise on the dynamic behavior of the MDNFL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of stochasticity can be attributed to internal and external noises. It is well known that noise can have great impacts on biological systems' dynamical properties (Lipshtat et al 2006;Hasty et al 2000;Vilar et al 2002;Rao et al 2002;Wang et al 2007;Li and Li 2008), for example, noise can induce sustained stochastic oscillation even though the corresponding deterministic system only yields steady state . In this paper, we have also studied the effect of extrinsic noise on the dynamic behavior of the MDNFL.…”
Section: Discussionmentioning
confidence: 99%
“…However, cellular processes at the molecular level are inherently stochastic (Balàsi et al 2011). Numerous studies have revealed the importance of stochastic or probabilistic effects in biological systems where the number of molecules is low enough for noise to be important, and the deterministic chemical kinetic descriptions are limited (Lipshtat et al 2006;Hasty et al 2000;Vilar et al 2002;Rao et al 2002;Wang et al 2007;Li and Li 2008). In addition, noise can also have significant effects on the stability and synchronization of genetic regulatory networks as well as neuronal networks (Shi et al 2008;Wang et al 2009;Guo 2011;Wu et al 2012).…”
Section: Stochastic Model and Noise-induced Dynamics For The Mdnflmentioning
confidence: 99%
“…We can describe this model in the following form [16]: (7) 13 illustrated in Fig. 5 indicates the origin of the bistability [15].…”
Section: The the The The Switching Switching Switching Switching Betwmentioning
confidence: 99%
“…However, in the case where small numbers of molecules are present, the modeling assumptions that give rise to the mass action ODE are not valid [11,12,22] and the discrete/stochastic effects captured by the CME should not be ignored. For example, the stochastic version of a bi-stable ODE model can account for switching between "almost stable" states [31,35].…”
Section: Introductionmentioning
confidence: 99%